Respostas
respondido por:
1
(Y/3)-(y/6)= (3.y/2)-(2)1/2. {(5)/(2) 1/2-(2) 1/2 (y)}
(Y/3)-(y/6) = (3.y/2)-5/2. {5/5/2 - 5/2 (y)}
mmc = 6
(2y/6) - (y/6) = (9y/6)-15/6.{10/5-5/2(y)}
(2y/6) - (y/6) = - 150/30 + 75/12 (Y)}
y/6 - (9y/6) - 75/12 (Y) = - 150/30
- 8y/6 = 75/12 (Y)
(Y/3)-(y/6) = (3.y/2)-5/2. {5/5/2 - 5/2 (y)}
mmc = 6
(2y/6) - (y/6) = (9y/6)-15/6.{10/5-5/2(y)}
(2y/6) - (y/6) = - 150/30 + 75/12 (Y)}
y/6 - (9y/6) - 75/12 (Y) = - 150/30
- 8y/6 = 75/12 (Y)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás